Leaf Anatomy and Chlorophyll Estimates in some Mangroves - Das, P. K.; Chakravarti, V.; Dutta, A.; Maity, S. (Indian Forester, 1995)
Four different tree species such as Ceriops tagal, Heritiera fomes, Nipa fruticans and Rhizophora apiculata commonly grown in mangrove swamps of Sundarbans, West Bengal, were studied for the leaf anatomy, stomatal characters and chlorophyll content. They displayed very distinct anatomical and stomatal modifications. The semi-mangrove, Nipa stood distinctly different from others. Of the halophytes, Heritiera showed deeply sunken stomata, covered by trichomes. It had more chlorophyll content and higher chlorophyll alb value, but had relatively small palisade-spongy ratio. The physiological significance of these modifications was discussed in relation to their specific adaptation to mangrove vegetation.